Analysis of Thermal Treatment Zirconia as Spacer Layer on Dye-Sensitized Solar Cell (DSSC) Performance with Monolithic Structure - Chairil Anwar; Erlyta Septa Rosa; Shobih Shobih; Jojo Hidayat; Dahlang Tahir (National Research and Innovation Agency, 2018)
Monolithic dye-sensitized solar cells (DSSC) offer the prospect of lower material cost and require a simpler manufacturing process compared with conventional DSSC. Fabricated on a single fluorine tin oxide (FTO) glass substrate consists of a nanoporous TiO2 photoanode layer, a ZrO2 spacer layer, a carbon counter electrode layer, a dye, and an electrolyte. The spacer layer on the monolithic DSSC serves as electrolyte storage and insulating layer to separate between photoanode and counter electrode. Zirconia is often used as a spacer because it has high temperature resistant properties, high dielectric constant and adhesive as an insulator that has band gap between 5-6 eV. The effects of the thermal treatment of zirconia layer as a spacer electrolyte on the performance of monolithic DSSC have been investigated. The cell’s performance increases with the sintering temperature as well as indicated by the decreased in particle size and increased in quantum efficiency in the absorption region of the titania layer. Co-sintering treatment tends to drastically reduce cell’s performance. The highest performance was obtained at a temperature sintering of 500o C with an PCE of 0.22%, Isc = 0.16 mA and Voc = 0.71 V.